Analysis of the Quality of Arabic Language Lesson Plans in Madrasah Aliyah Based on the National Curriculum - Tiwi Lestari; Ediat Ediat; Nadzifa Milata Hanifa; Iffatun Thoyyibah (Gunung Djati Conference Series, 2026)
This study aims to (1) determine the alignment of Arabic Language Lesson Plans (RPP) in Madrasah Aliyah with the standards of the current National Curriculum, (2) assess the quality of learning objectives, instructional materials, methods, and assessment components in the Arabic RPP based on National Curriculum principles, (3) analyze the factors influencing the quality of RPP development and implementation by teachers, (4) describe the implementation of the RPP in classroom learning activities, and (5) identify the challenges teachers face in developing RPPs in accordance with regulations, as well as the efforts undertaken to overcome these challenges. The research adopts a descriptive qualitative approach using interviews, observations, and documentation, followed by data analysis through the Miles and Huberman model and triangulation techniques to ensure data validity. The findings show that the conformity and overall quality of the RPPs fall into the “adequate” category, yet they are not optimal in implementing the scientific approach, integrating Higher-Order Thinking Skills (HOTS), and conducting authentic assessments. The quality of the RPPs is influenced by teachers’ understanding of the curriculum, pedagogical competence, and their ability to adapt instruction to students’ needs. Classroom implementation still relies heavily on teachers’ creativity in fostering communicative and character-oriented learning activities. Major challenges include limited training, difficulties in formulating measurable indicators, and minimal academic supervision. Efforts to address these issues are carried out through continuous professional development, MGMP (subject-teacher forum) collaboration, and institutional support aimed at improving the alignment of the RPP with National Curriculum requirements and 21st-century learning demands.